Factors Related to Food Waste Disposal Behavior of Students in the Dormitory of STIKes Santa Elisabeth Medan - Pane, Jagentar; Simorangkir, Lindawati; Sitompul, Iralomal Oktavia (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Food waste occurs when perfectly edible food is discarded for various reasons. Factors contributing to food waste include menu neglect, excess preparation, unappealing appearance, and inaccurate perceptions of taste. Reducing food waste can be achieved by valuing food as an essential aspect of human life and managing food consumption effectively. Based on a survey conducted in dormitories, the significant issue identified is the daily abundance of leftovers, including 4-6 buckets of vegetables, tempeh, and tofu, mainly due to the food needing to meet the students' tastes. This study examines the factors influencing food waste disposal behaviour among students at the STIKes Santa Elisabeth Medan dormitory in 2023. The study utilized a cross-sectional approach combined with correlational research and involved 84 students living in the dormitory. The research instruments included a Food Waste Questionnaire and a Food Scales Questionnaire. Data analysis involved using Chi-square tests to determine the relationship between independent variables of food appearance and taste factors and the dependent variable of food waste behaviour. The results revealed a significant relationship between unattractive food appearance and high food waste, with 90.4% demonstrating high waste and 9.6% showing low waste, as confirmed by a Chi-square value of 455 and a p-value of 0.05. In conclusion, this study found a notable association between unattractive food appearance and the disposal behaviour of dormitory students regarding food waste.